Where do herbivore-induced plant volatiles go? - Holopainen, Jarmo K.; Blande, James D. (Frontiers in Plant Science, 2013)
Herbivore induced plant volatiles (HIPV) are specific volatile organic compounds (VOC) that a plant produces in response to herbivory. Some HIPVs are only produced after damage, while others are also produced by intact plants, but in lower quantities. Among the known functions of HIPVs are within plant volatile signalling to activate systemic plant defences, the priming and activation of defences in neighbouring plants and the attraction of natural enemies of herbivores. When released into the atmosphere a plant’s control over the produced compounds ends. However, many of the HIPVs are highly reactive with atmospheric oxidants and their atmospheric life times could be relatively short, often only a few minutes. We summarise the potential ecological and atmospheric processes that involve the reaction products of HIPVs in their gaseous, liquid and solid secondary organic aerosol (SOA) forms, both in the atmosphere and after deposition on plant surfaces. A potential negative feedback loop, based on the reactions forming SOA from HIPV and the associated stimulation of sun screening cloud formation is presented. This hypothesis is based on recent field surveys in the geographical areas facing greatest degree of global warming and insect outbreaks. Furthermore, we discuss how these processes could benefit the individual plant or conspecifics that originally released the HIPVs into the atmosphere. Further ecological studies should aim to elucidate the possible reasons for biosynthesis of short-lived volatile compounds to have evolved as a response to external biotic damage to plants.